Differences in edge artifacts between 68Ga- and 18F-PET images reconstructed using point spread function correction. Issue 11 (November 2019) - Amakusa, Shinji; Matsuoka, Koki; Baba, Shingo; Yoshida, Tsuyoshi; Sasaki, Masayuki
Abstract : Objective: Edge artifacts have been reported on in relation to 18 F-PET using point spread function correction algorithms. The positron range of 68 Ga is longer than 18 F, and this difference is thought to result in different edge artifacts. The purpose of this study is to clarify the difference in edge artifacts in PET images using point spread function correction in 68 Ga- and 18 F-PET. Methods: We used a National Electrical Manufacturers Association International Electrotechnical Commission body phantom. The phantom was filled severally with 68 Ga and 18 F solution. The PET data were obtained over a 90 minutes period using a True Point Biograph 16 scanner. The images were then reconstructed with the ordered subset expectation maximization with point spread function correction. The phantom image analyses were performed by a visual assessment of the PET images and profiles, and an absolute recovery coefficient, which was the ratio of the maximum radioactivity of any given hot sphere to its true radioactivity. Results: The ring-like edge artifacts of 68 Ga-PET were less prominent than those in 18 F-PET. The relative radioactivity profiles of 68 Ga-PET showed low overshoots of the maximum radioactivity although high overshoots did appear in 18 F-PET. The absolute recovery coefficients of 68 Ga-PET were smaller than those of 18 F-PET. Conclusion: The edge artifacts of 68 Ga-PET were less prominent than those of 18 F-PET, and their overshoots were smaller. The difference in the positron range between 68 Ga and 18 F may possibly result in the difference in edge artifacts of images reconstructed using the point spread function correction algorithm.